Relative validity of a semi-quantitative food frequency questionnaire to estimate the intake of iron and its absorption modifiers in young Saudi females - Almaghrabi, Merfat; Albar , Salwa; Alsufiani , Hadeil; Zamkah , Ranim; Alyafie, Sarah; Houssien, Abrar (Progress in Nutrition, 2022)
Background and aim: To date, there is a lack of published data regarding validated food frequency questionnaire (FFQ) design specifically for Saudi populations. Therefore, the purpose of this study was to investigate for the first time the relative validity of a semi-quantitative FFQ to estimate the intake of iron and its absorption modifiers in young Saudi females. Methods: A convenience sample of 101 apparently healthy young Saudi females aged 18- 24 from Jeddah, Saudi Arabia participated in the study. All participants completed the FFQ and three non-consecutive days of food records (FR) to determine validity. Pearson’s correlation was used to investigate the correlation between nutrients intake obtained from the FFQ and FR. The agreement between the two methods was compared using a Bland-Altman analysis and the Cohen’s kappa statistic. For the analysis, the significance level was set at p <0.05. Results: There were no significant differences between the estimates of iron and calcium intake obtained by the two methods. However, the FFQ yielded higher estimates of vitamin A, vitamin C, and fiber. The differences in iron was equivalent to 4%, with agreement ranging from an underestimation of 1.2% to an overestimation of 1.3%. For vitamin A, vitamin C, and fiber, the difference between the two methods increased with increasing mean intake. The agreement on ranking showed that participants were correctly classified in the same or adjacent quantile of nutrient intake. Conclusions: The semi-quantitative FFQ appears to be a reasonably valid method of estimating the intake of iron and its absorption modifiers in young Saudi females. The present findings are of interest for public health and could be applied in epidemiological studies.